1996
DOI: 10.1039/cc9960001113
|View full text |Cite
|
Sign up to set email alerts
|

N7, O6bridging 9-ethylguanine (9-EtGH) groups in dinuclear metal–metal bonded complexes with bond orders of one, two or four

Abstract: Dinuclear metal carboxylates of Mo, Ru and Rh with 2 equiv. of 9-ethylguanine (9-EtGH) give complexes containing [M~(O~CR)~(~-E~GH)~(SO~V)~]~+ cations; structural characterization shows these to contain unusual N7,06-bridging 9-EtGH groups in 'head-to-tail' (HT) or 'head-to-head' (HH) orientations, and establishes this bridging mode for metal-metal bond orders of 1-4.The antitumour activity of cisplatinl has prompted extensive investigation into its mechanism of action and into the development of other metal-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
55
0
2

Year Published

2005
2005
2007
2007

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 50 publications
(58 citation statements)
references
References 17 publications
1
55
0
2
Order By: Relevance
“…The X-ray crystal structure of [(g 6 -p-cym)Ru(Ph 2 acac)9EtG-N7]CF 3 SO 3 AE 2tol (5 AE 2tol) shows binding of ruthenium to N7 of 9EtG in accordance with the solution studies. The Ru-N7 distances of 2.126(3) Å and 2.140(3) Å for both molecules in the asymmetric unit in the structure of 5 AE 2tol are at the higher end of the range for known Ru II complexes containing bound guanine derivatives [35][36][37], including Ru II arene complexes [7,11,14,38,39]. Thus the comparatively weaker interaction observed in solution appears to be reflected in the solid state structure.…”
Section: Discussionmentioning
confidence: 69%
“…The X-ray crystal structure of [(g 6 -p-cym)Ru(Ph 2 acac)9EtG-N7]CF 3 SO 3 AE 2tol (5 AE 2tol) shows binding of ruthenium to N7 of 9EtG in accordance with the solution studies. The Ru-N7 distances of 2.126(3) Å and 2.140(3) Å for both molecules in the asymmetric unit in the structure of 5 AE 2tol are at the higher end of the range for known Ru II complexes containing bound guanine derivatives [35][36][37], including Ru II arene complexes [7,11,14,38,39]. Thus the comparatively weaker interaction observed in solution appears to be reflected in the solid state structure.…”
Section: Discussionmentioning
confidence: 69%
“…A color change from blue to green occurred within 3 days. The N7/X6 (X = O in G, X = N in A) nucleobase bridging modes of the A‐ or G‐bound products shown in Scheme were based on X‐ray single crystal and NMR structure determinations of dinuclear metal complexes coordinated to model purine bases 14. The purine binding modes of complexes 2 and 3 have not been unambiguously determined in this present study.…”
Section: Resultsmentioning
confidence: 77%
“…Findings in our laboratories have shown that adenine and guanine bases bind to the dirhodium core in an alternative manner that involves displacement of eq bridging groups. The crystal structure Figure 8) 42 revealed the presence of unprecedented bridging guanine groups spanning the dirhodium unit via N7/O6 in a cis disposition and H-H or head-to-tail (H-T) 43 orientations. These X-ray studies provided the first hard evidence for guanine O6 participation in binding to dimetal units.…”
mentioning
confidence: 99%